Muscle‐specific functional deficits and lifelong fibrosis in response to paediatric radiotherapy and tumour elimination. Issue 1 (8th January 2022) - Kallenbach, Jacob G.; Bachman, John F.; Paris, Nicole D.; Blanc, Roméo S.; O'Connor, Thomas; Furati, Esraa; Hernady, Eric; Johnston, Carl J.; Williams, Jacqueline P.; Chakkalakal, Joe V.
Abstract: Background: As paediatric cancer survivors are living into adulthood, they suffer from the age‐related, accelerated decline of functional skeletal muscle tissue, termed sarcopenia. With ionizing radiation (radiotherapy) at the core of paediatric cancer therapies, its direct and indirect effects can have lifelong negative impacts on paediatric growth and maintenance of skeletal muscle. Utilizing our recently developed preclinical rhabdomyosarcoma mouse model, we investigated the late effects of paediatric radiation treatment on skeletal muscles from late adolescent (8 weeks old) and middle‐aged (16 months old) mice. Methods: Paediatric C57BL/6J male mice (3 weeks old) were injected with rhabdomyosarcoma cells into their right hindlimbs, and then fractionated irradiation (3 × 8.2 Gy) was administered to those limbs at 4 weeks old to eliminate the tumours. Radiation‐alone and tumour‐irradiated mice were assessed at either 8 weeks (3 weeks post‐irradiation) or 16 months (14 months post‐irradiation) of age for muscle physiology, myofibre characteristics, cell loss, histopathology, fibrosis, inflammatory gene expression, and fibrotic gene expression. Results: Mice that received only paediatric radiation demonstrated reduced muscle mass (−17%, P < 0.001), muscle physiological function (−25%, P < 0.01), muscle contractile kinetics (−25%, P < 0.05), satellite cell number (−45%, P < 0.05), myofibre cross‐sectional area (−30%, P < 0.0001), and myonuclear number (−17%, P < 0.001). Paediatric radiation increased inflammatory gene expression, increased fibrotic gene expression, and induced extracellular matrix protein deposition (fibrosis) with tumour elimination exacerbating some phenotypes. Paediatric tumour‐eliminated mice demonstrated exacerbated deficits to function (−20%, P < 0.05) and myofibre size (−17%, P < 0.001) in some muscles as well as further increases to inflammatory and fibrotic gene expression. Examining the age‐related effects of paediatric radiotherapy in middle‐aged mice, we found persistent myofibre atrophy (−20%, P < 0.01), myonuclear loss (−18%, P < 0.001), up‐regulated inflammatory and fibrotic signalling, and lifelong fibrosis. Conclusions: The results from this paediatric radiotherapy model are consistent and recapitulate the clinical and molecular features of accelerated sarcopenia, musculoskeletal frailty, and radiation‐induced fibrosis experienced by paediatric cancer survivors. We believe that this preclinical mouse model is well poised for future mechanistic insights and therapeutic interventions that improve the quality of life for paediatric cancer survivors.